Kısa vadeli sermaye hareketleri ile faiz arasındaki ilişki - Kara, Hakan (Sosyal Bilimler Enstitüsü, 2012)
Dünya ekonomisinde özellikle 20 yy. da hızla küreselleşme ve serbestleşme adımları atılmıştır. Bu adımlar mal ticaretindeki hacmi arttırmaktan daha çok finansal akımları arttırmıştır. Yeni düzende küreselleşmeyle dünyada dönen para, hem nominal olarak hem de oransal olarak finans sektöründe yoğunlaşmıştır. Neredeyse karşılaştırılamayacak şekilde mal ve hizmet ticaretinden finans sektörüne kayan sermaye, dünya ekonomisini ciddi anlamda tehdit etmektedir. Tasarruf fazlası bulunan gelişmiş ekonomilerdeki kâr paylarının daralması bu ekonomileri yeni arayışlara sokmuştur. Bu arayışla kendi ülkelerinden başlayarak dünyaya yeni bir sistem empoze etmişlerdir. Kuşkusuz dünyadaki bu büyük ekonomik değişim ve dönüşüm kendisini dünyadan soyutlamamış bütün ülkelerde farklı zaman aralıklarında gerçekleşmiştir. Bu gelişmelerden Türkiye de etkilenmiştir. Bu amaçla Türkiye finansal ve mali yönden dünya ile bütünleşmesini tamamlamak adına 1980'den sonra birçok düzenleme yapmıştır. Dış finansal serbestleşmenin de tamamlanmasıyla spekülatif sermaye girişlerine tamamen açık hale gelen Türkiye, ciddi miktarlarda ani sermaye giriş çıkışlarına maruz kalmış ve makroekonomik göstergeler oynak hale gelmiştir. Dünyadaki gelişmelerden doğrudan etkilenir hale gelen Türkiye, bu süreçten sonra 1994 ve 2001 yıllarında iki büyük kriz yaşamıştır. 1994 yılında artan kamu borçlarının yanı sıra faizler düşürülünce, ani sermaye çıkışları olmuş ve istenilenin aksine faizler aşırı yükselmiştir. 2001 yılında orta ölçekli yerli bir banka, bulunduğu zor durumdan kurtulmak için, elindeki devlet iç borçlanma senetlerini ikinci el piyasada satınca faizler yükselmiştir. Buna karşın yabancı yatırımcılar ve diğer bankalar da zararlarını kapatmak için satışta bulunmuşlardır. Merkez Bankası'nın başlangıçta likidite sağlaması yabancıların Türk ekonomisine olan bakışını değiştirmemiş çıkış devam etmiştir.Bu çalışmada Türkiye'nin Aralık 1991 ile Mart 2011 tarihleri arasındaki Türkiye'deki gecelik faiz oranları ile ödemeler dengesi kalemlerinden düzenlenen kısa vadeli sermaye hareketleri arasındaki ilişki, ekonometrik yöntemler kullanılarak incelenmiştir. Çalışmada kullanılan verilerin zaman serisi olmasından ve birçok zaman serisinin trend içerdiği bilindiğinden dolayı, doğru sonuca ulaşabilmek için öncelikle bu çalışmada kullanılan serilerin de trend içerip içermediği birim kök testleri ile sınanmıştır. Serilerin zaman içinde birlikte nasıl hareket ettiğini ve aralarında bir nedensellik olup olmadığı yapısal kırılmalı eşbütünleşme ve Toda-Yamamoto testi ile araştırılmıştır. Kısa vadeli sermaye hareketleri ile gecelik faiz arasında Temmuz 2000 öncesi anlamlı bir ilişki bulunamazken Temmuz 2000 ve Mart 2011 tarihleri arasında negatif yönlü ve anlamlı bir ilişki bulunmuştur. Bununla birlikte seriler arasında iki yönlü nedensellik ilişkisi olduğu tespit edilmiştir.

The beginning of economic globalization in the World is considered as the mid nineteenth century. By means of new inventions, the countries that accomplished industrial revolution had started to produce more than their need so they had begun to search for new markets in order to trade them. As it comes to 20th century, World?s trade has firmly shifted in favor of industrialized countries. In this century, large portion of trade volume had been among developed countries. When emerging needs for capital as a result of growing trade volume couldn?t be satisfied with gold standard, banknotes had been widespread and their circulation had increased. The shift towards developed countries in increasing economic surplus and spreading banknotes had emerged ambiguity during exchange between national currencies because occurring economic surplus couldn?t be expressed by gold or other similar real goods. These ambiguities had caused negligence in financial system and encourage the speculative monetary movement move away from real production. First destructive effect of increase in these monetary movements which is disconnected from real production become apparent by the damage of great depression and had been understood how destructive it is. In order to refrain from the similar damages caused by great depression, Bretton-Woods? system had accepted. Bretton-Woods? system had restrained the speculative movements by putting regulations against fixed exchange rate and monetary movements. By cancellation of Bretton-Woods? system, world entered into new liberalization period which can be counted as second globalization phase. This period had spread quickly to countries by uniting with technological developments and become more open to outside impacts.Together with the collapse of Bretton-Woods? system, countries quickly entered into liberalization period. Some countries carry out the liberalization process gradually, while some others achieved sudden transition. Before opening outside in order to take necessary precautions and reduce the probable negative effects, inside financial liberalization movements had begun. Countries in this concept made regulations about important fields as banking system. After inside liberalization had occurred, they have achieved outside financial liberalization by providing outside source to cover insufficient inside saving gap in order to support investment and development. Liberalization of monetary movement which is the most important step of opening outside quickened the monetary movement from the countries with surplus capital to the countries in need of capital. International short-term capital movement (STCM) flow which shelters speculative features had been increasing day to day. This situation almost makes it impossible for the countries to set up independent policies in the interest of their own.Turkey?s financial liberalization and integration with world had started to gain momentum by the rule of January 24, 1980. Consecutive fiscal and financial regulation had resulted with extensive regulation in exchange regime at 1989. Some of the regulations are explained below;?Any action related to foreign exchange is released.?Foreign exchange of those who reside in Turkey and opening accounts for non-residents has been released.?Restriction to money transfer from domestic to abroad or abroad to domestic for both sides has been abolished.Thus, Turkey is now acting together with the World in financial point to become a country without restriction of monetary movement and to become open to outside influences. After these changes, capital circulation around the globe can make sudden in and out to Turkey in order to provide more earnings and overcome profits-squeeze in developed countries. However, this situation can cause negative influences on macroeconomic indicators like inflation, foreign currency and interest.There was an expectation that capital could tend to go to the countries which give higher interest rate and these countries? interest rate would come to same level with freed monetary movements. Expectation in theory and reality displayed differences among countries. In this study, relationship of short term capital and interest in Turkey has been investigated by using the data between December 1991 and March 2011.This study?s first section is introduction, that gives general information about this study?s parts. In second section, study mentions briefly the financial liberalization stages in the world. Later, it mentions fiscal and financial steps that Turkey has done in order to ensure compliance with world. It also mentions on which institution has started the action of in and out financial liberalization and some basic regulations done in order to keep up with the existing order. For example, Capital Markets Board has been established with necessary legal changes. Besides that, Istanbul Stock Exchange has become active again. While the number of foreign bank inside Turkey was three in 1980, this number became eight in 2000. In third section, study mentions the term of short term capital movement?s scope, definition, causes and consequences. Internal and external reasons of determination of STCM are also mentioned. There are certain indicators of internal factors for capital flows to come to the country. According to the gross domestic product rate, diminution of volatility at higher investment, lower inflation and real exchange rate helps seriously for the countries to draw capital to themselves. But countries not robust about these values are unable to draw capital. In addition to that, interest rate is also important for capital inflow. Direct investment is insensitive to interest rate; Portfolio currents are more sensitive to interest rate. Inclination of foreign capital to developing countries and external factors are also important as internal factors. As a result of fall on interest rate in developed countries, investors tend to search for ways to gain more earning. This situation tends capital to flow into developing countries. In addition, STCM?s effect on mainly macroeconomic indicators like inflation, investment-consumption foreign exchange reserves and payment balance are explained. While short term capital movement directly effects one country?s some part of macroeconomic balance, affects indirectly many of the others. Expression of this effect on this section are addressed separately as interactions although it is not separated certainly from each other, short term capital movement?s effects on known macroeconomic balance. In forth section, study mentions about the description of interest, interest rate and interest types. Difference of nominal and real interest is expressed as it is important for investors. Beside these, factors that affect interest rate are also mentioned. Factors like how money supply and payment structure are affecting interest rate with which channel and with which ways are expressed in the study.Fifth section that mentions data and econometric procedure, primarily information about functioning of extended Dickey-Fuller (ADF, Augmented Dickey Fuller, 1981) and KPSS (Kwaitkowski, Phillips, Schmidt and Shin, 1992) unit root tests. Unit root tests are done in order to identify whether series are stable or not because the studies done with unstable series show that it can be faced with spurious regression problem. In other words, in reality variables that have no connection with each other could be seen as connected with series, since they are not stable. No unit root test can give exact result by itself. Therefore, new tests are brought in order to cover the other gaps. Zivot-Andrews (1992) for single internal fracture, Lee-Strazicich (2003) for double internal fracture unit root tests are mentioned which takes into account the structural breaks at continuation of analyze to reduce the failure portion. Under structural fracture of stages of co-integration analyses are explained which is developed by Kejriwal-Perron (2008) in order to be used for detection of long term connection between series according to stability level of series dealt with in the content of analysis. Kejriwal-Perron (2008) provides opportunity for analyzing of relationship among series by seting up breaking date. At the end of this section, to determine the direction of connection of among hot money and nightly interest rate series, Toda-Yamamoto (1995) linear Granger type causality analyses are explained. In addition to these, in this this section, findings from former studies about relationship between STCM with interest made for Turkey and other countries are expressed. Contrary to the theory, different results were obtained from empirical studies done for both Turkey and World. As a result of policies applied in order to diminish the effect of capital inflow that is held in high amount in many different countries, interest didn?t move towards desired direction. Especially, as a result of sterilization policies, it is determined that interest rate has increased higher. In this concept, it is observed that in some part of the research relation?s positive side is found while in others negative side is found. At the end of this section, the results of the test done are evaluated. As a result of ADF and KPSS tests, nightly interest series is calculated as stable level and hot money series is calculated as first degree stable. Structural fracture unit root test series gives the result that it includes unit root. These test results are commented as economically. When the years that structural fracture has happened are examined, it is detected that the dates are not only important for Turkey but also they are the times which are economic and political development that happened in the World. These findings are economically reasonable when we consider the behavioral aim and capability of hot money. As a result of structural fracturing co-integrated Kejriwal and Perron test, July 2000 is found as fracture date. Connection between STCM and interest rate are examined by separating them into two periods. In first period, pre-july 2000, there is no significant relation but in second period, there is a relation in negative direction. At last, two-way causality is found as a result of Toda and Yamamota causality test.
Relationship between short term capital movement and interest
Keywords: Faiz , Kısa vadeli sermaye , Nedensellik testleri , Sermaye , Sermaye hareketleri ,Yapısal kırılmalar; Unit root ,Interest, Short term fund , Causality test ,Capital , Capital movements ,Structural breaks